2023
DOI: 10.1186/s12913-023-09352-4
|View full text |Cite
|
Sign up to set email alerts
|

“But at home, with the midwife, you are a person”: experiences and impact of a new early postpartum home-based midwifery care model in the view of women in vulnerable family situations

Abstract: Background Postpartum home-based midwifery care is covered by basic health insurance in Switzerland for all families with newborns but must be self-organized. To ensure access for all, Familystart, a network of self-employed midwives, launched a new care model in 2012 by ensuring the transition from hospital to home through cooperation with maternity hospitals in the Basel area. It has particularly improved the access to follow-up care for families in vulnerable situations needing support beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Secondly, socio-economic determinants are marked by an increased prevalence of women with a migrant background 14 , 15 , delayed maternal age at childbirth 16 , and residence in socially deprived conditions 17 , 18 . These phenomena are correlated with elevated rates of adverse maternal and neonatal outcomes.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, socio-economic determinants are marked by an increased prevalence of women with a migrant background 14 , 15 , delayed maternal age at childbirth 16 , and residence in socially deprived conditions 17 , 18 . These phenomena are correlated with elevated rates of adverse maternal and neonatal outcomes.…”
Section: Commentarymentioning
confidence: 99%
“…They emphasize the need for recognizing the APN service as independent and billable to support primary healthcare sustainably 49 . In the Swiss canton of Basel, Schwind et al 18 evaluated the impact of de facto APM care within the SORGSAM (Support at the Start of Life) project in 2023 for families in vulnerable situations. The authors demonstrated how offering improved assistance to psychosocially and economically disadvantaged families enhances parental resources, leading to better postpartum health outcomes for mothers and children.…”
Section: Commentarymentioning
confidence: 99%